Variation of Transport Properties and Apparent Density of Soft Nickel Ferrite (Journal of Bangladesh Academy of Sciences, 2012)
Polycrystalline NiFe2O4 was prepared from Analytical Grade powder of NiO and Fe2O3 by conventional double sintering technique. The apparent density of the prepared sample increases with the increase in sintering temperature and consequently the porosity decreases which has a great influence on electrical and dielectric properties of soft ferrites. It is observed that with the increase in temperature, the DC resistivity of the prepared sample decreases which confirms the semiconducting behavior of the prepared NiFe2O4. In addition to this, at room temperature it is observed that the resistivity decreases with the increase in sintering temperature. Variations of activation energy have been observed for different sintering temperature and are in agreement with the resistivity measurement. Frequency dependence of dielectric constant (?) has been measured and shows the normal dielectric behavior of the prepared sample which can be explained on the basis of Koops two layer model and Maxwell-Wagner polarization theory. Along with these, enhancement of dielectric constant has been observed with the increase in sintering temperature. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10929 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 137-142, 2012